2017
DOI: 10.29063/ajrh2017/v21i4.5
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence and HIV Status among Ever-Married and Cohabiting Zimbabwean Women: An Examination of Partners’ Traits

Abstract: This study examines the connection between intimate partner violence (IPV) and Human Immunodeficiency Virus status among married and cohabitating women in Zimbabwe using an African feminist framework. Stata 13.0 was used to analyze data from the 2010-2011 Zimbabwe Demographic and Health Survey, which used a national probability sample of households in the country of Zimbabwe. This study used logistic regression to analyze the 2,830 ever-married or cohabitating women who also answered the violence and spousal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…The male partner of women with a known history of HIV had significantly higher acceptance of intimate partner violence. This is in line from a study among married and cohabitating women in Zimbabwe that found that women had experienced any form of intimate partner violence were more likely to be HIV positive 29 , HIV positive women reported 30 , and in India, HIV positive women were three times more likely to experience sexual violence compared to HIV negative women 31 .…”
Section: Discussionsupporting
confidence: 83%
“…The male partner of women with a known history of HIV had significantly higher acceptance of intimate partner violence. This is in line from a study among married and cohabitating women in Zimbabwe that found that women had experienced any form of intimate partner violence were more likely to be HIV positive 29 , HIV positive women reported 30 , and in India, HIV positive women were three times more likely to experience sexual violence compared to HIV negative women 31 .…”
Section: Discussionsupporting
confidence: 83%
“…For example, Zegeye et al (2021) argue that acceptance of IPV in Senegal is driven by deep rooted cultural beliefs that men are superior, and women are subordinate. Henderson et al (2017) argue that IPV is acceptable in Zimbabwe within a hypermasculinist, militaristic environment. In these cultural contexts, mere possession of a title may have no impact on IPV.…”
Section: Resultsmentioning
confidence: 99%
“…Hyper-masculinity disregards women's rights and supports patriarchal norms that allow for the male dominance of women . Although research on DV and IPV in urban Zimbabwe has been accumulating (Fidan & Bui, 2016;Henderson et al, 2017;Shamu et al, 2018), information on the support systems available for women residing in rural areas remains limited regardless of the vulnerabilities to which they are exposed. Consequently, there is scant knowledge of the public support systems for IPV victims in rural areas.…”
Section: Key Examples Of Policing Challenges In Rural Zimbabwementioning
confidence: 99%